Leveraging Indigenous Resources: A Digital Communication Framework for the Omah Wayang Tourism Village in Sidowarno - Joko Suranto (Javanologi: International Journal of Javanese Studies, 2025)
This research investigates the strategic implementation of local potential through digital communication channels at the Omah Wayang tourism village in Sidowarno Village, Juwiring District, Klaten Regency. The study addresses the critical challenge of underutilized cultural resources and tourism potential within the region, with particular emphasis on Omah Wayang, a community organization dedicated to preserving and transmitting the philosophical and artistic values of traditional shadow puppetry (wayang). More than just an art form, wayang embodies profound Javanese wisdom such as pitutur luhur (moral advice), balance (keseimbangan), and harmony (rukun), which are continually passed down through intergenerational learning at Omah Wayang. Through a qualitative descriptive methodology, incorporating systematic field observations and in-depth stakeholder interviews, this research examines indigenous assets such as traditional crafts, culinary heritage, and cultural performances. The investigation expands beyond puppetry to explore how broader cultural expressions can be strategically incorporated into digital communication practices. The findings present actionable strategies for enhancing tourism visibility through culturally grounded digital platforms while ensuring the authenticity and sustainability of local traditions. This study contributes to local economic revitalization and the preservation of intangible heritage, offering a replicable digital communication framework that bridges traditional knowledge systems with contemporary tourism promotion. The research emphasizes the importance of community-based institutions like Omah Wayang in mediating between cultural continuity and innovation in the digital era